A Review of the fiscal stimulus plan taken by the Chinese government in 2008 - Feng, GAO (KDI School, 2011)
The 4-trillion RMB fiscal stimulus plan carried out by the Chinese government in late 2008 is illustrated in this paper as regard to its background, sources and uses. A comparison between the 2008 stimulus and the previous stimulus initiated in 1998 by the Chinese government is drawn. Then the stimulus package was analytically approached by using IS-LM model. A simple regression method is also applied to check how much expectation links to growth. Some relevant data seem to indicate the preliminary effects of the 2008 stimulus package. The practices of Chinese government’s stimulus plan could shed light on some important aspects of economic policy.
Thesis(Master) --KDI School:Master of Public Policy,2011
Keywords: China.